Ritual, Symbol, and Experience: Understanding Catholic Worker House Masses - Spickard, James V. (Sociology of religion, 2005)
This article uses house masses in a Catholic Worker community to examine the interaction of symbols and experience in religious rituals. It argues that, during the period of this study, these weekly masses served to reinforce Worker identity by guiding participants' experiences along specific lines. Ritual symbolism and the moment-to-moment attention of the participants combined to move participants from despair at the state of the world to an experience of a community of solidarity and hope. A second phase of the ritual then expanded that community to include homeless people, by means of a symbolic second ‘mass’ of soup, bread, and water, delivered in the streets. The article demonstrates the need for sociology to consider the experiential dimension, along with the symbolic, in understanding rituals' role in religious life.